Sustainable Community Enterprise Development Policy to Strengthen the Local Economy - Chanyam, Tanakorn; Mola, Anuchit; Wongwatthanaphong, Kampanart (Interdisciplinary Academic and Research Journal, 2023)
A policy to revitalize the economic situation of the government sector that will generate appropriate business practices, especially the concept of community enterprise (Community Enterprise) for the sustainable development of the community’s economy. From that concept, it has resulted in a way to develop a strong community economy to create a mechanism to compete with both the domestic market and the international market even more. This study, therefore, has the following objectives; (1) to Study the development of sustainable community enterprises, and (2) a study strengthening the grassroots economy. The study of sustainable community enterprise development is a study of the principles, the history of community enterprises in Thailand and the study of the components of sustainable community enterprises, which consist of 4 elements: marketing, production, finance, and management as well as studying strengthening the grassroots economy as a study of meanings, principles, and drives for strengthening the integrated economy, with the participation of many sectors, including government, private sector, education and academic sector, civil society, and community enterprise or community business. The results show that the components of community enterprises are marketing, production, finance, and management. All of them are important and affect the operation to build a community enterprise to be strong and self-reliant according to the concept of stability, prosperity, and sustainability. As for the strengthening of the grassroots economy, all sectors must participate in an integrated way. All sectors are connected to drive the strengthening of the grassroots economy of the local community. And to elevate the economy, and society, and create income stability. This has resulted in the development of the quality of life of members and people in local communities to live well, eat well, and have good physical and mental health.